Analytical Investigation on Improving Safety Performance in Construction Sites (International Journal of Innovative Research in Engineering & Management, 2022)
Construction industries are known to be  hazardous due to complex tasks, change of work location,  climatic conditions and temporary organizational  management. The consequences of these hazards may  involve occupational diseases, injuries and fatality. Injuries  and accident rates are high in a construction site when  compared with other manufacturing industries. Safety is  one of the key factors in construction sites to mitigate the  severity of the risk. Assessing the performance of the site  concerning safety is an important part of the management  system as it provides information on the safety of the  worker as well as the task. Hence the aim of this research  is to investigate the site safety performance and propose a  methodology for enhancement. This is done in basically  four parts viz., quantification of risk involved in each task,  accounting for unsafe supervision, selection of right  worker for the right task and usage e.g., PPEs. Safety  performance cannot be measured only with the  accidents/injuries in the site but the factors which influence  the unplanned events have to be highlighted while  determining the performance rate. The factors include the  task/conditions of the site. Risk involved in each task is  quantified using Hazard Identification and Risk  Assessment (HIRA) technique. The hazards in the sites are  identified through direct observation and previous safety  reports and the risk values are determined using likelihood  and severity ratings of each hazard. It is known that the  construction site has 13.3% of low risk, 37.7 % of medium  risk, 44.4 % of high risk and 4.6 % of extreme risk. The  relative percentage of risk involved in each task is  calculated and it is found that crane operation (10.4%),  height work (9.1%) and drilling (8.8%) are the three major  tasks with high risk. It is observed that in the particular  construction site the relative percentage of low risk is very  less. Furthermore, it can be said that by task-based risk  quantification the builders/owners may look for suitable or  alternate control measures to reduce the risk level to as low  as reasonably practicable. This will automatically improve  the performance of the site.
Keywords: Construction Dust; Construction Noise; Personal Protective Equipment